MODELING OF SUBSURFACE HORIZONTAL POROUS PIPE IRRIGATION UNDER DIFFERENT CONDITIONS - Rasheed, Z. K. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
Horizontal porous pipe method is one of the most efficient systems of irrigation in arid and semi-arid areas.  The main aim of this study is to simulate the subsurface horizontal porous pipe irrigation under different conditions.  By this method of irrigation, an optimum amount of water is reached to the crop.  Moreover, it saves more water than the other irrigation systems.  Simulation models by HYDRUS/2D  are described the distribution of wetting shapes in two different soil textures through the system of United States Department of Agriculture, USDA, namely as loam and silt soils.  The system is designed for three diameters of 6, 7, and 8 cm installed at 15, 20, and 25 cm below the soil surface under three application heads of 25, 50, and 75 cm.  Horizontal and vertical advance of the wetting front shapes in loam are greater than silt soil.  The numerical values of horizontal and vertical advance are compared with those of predicted by the formulas, showing that average relative error values not more than 2 %.  This indicated that the formulas may be used as a tool for designing and investigating the subsurface horizontal porous pipe irrigation system.